2017
DOI: 10.1017/s0950268817002011
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence ofClostridium difficileinfection and colonization in a tertiary hospital and elderly community of North-Eastern Peninsular Malaysia

Abstract: Little is known about Clostridium difficile infection (CDI) in Asia. The aims of our study were to explore (i) the prevalence, risk factors and molecular epidemiology of CDI and colonization in a tertiary academic hospital in North-Eastern Peninsular Malaysia; (ii) the rate of carriage of C. difficile among the elderly in the region; (iii) the awareness level of this infection among the hospital staffs and students. For stool samples collected from hospital inpatients with diarrhea (n = 76) and healthy communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Due to uncertainty about whether they were carried with a toxigenic strain, cases, where they were isolated, were excluded from the logistic regression analyses. The prevalence of colonization with non-toxigenic strains in Asian countries appears to be high among hospital inpatients (10.4-28.6%) [15][16][17]27,41]. This is interesting given that clinical trials have found that administration of non-toxigenic strains reduces risk of recurrent infection in CDI cases [42], making it plausible that the high prevalence of colonization with non-toxigenic strains in Asia-Pacific countries may explain the low rate of recurrent CDI found in this study.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Due to uncertainty about whether they were carried with a toxigenic strain, cases, where they were isolated, were excluded from the logistic regression analyses. The prevalence of colonization with non-toxigenic strains in Asian countries appears to be high among hospital inpatients (10.4-28.6%) [15][16][17]27,41]. This is interesting given that clinical trials have found that administration of non-toxigenic strains reduces risk of recurrent infection in CDI cases [42], making it plausible that the high prevalence of colonization with non-toxigenic strains in Asia-Pacific countries may explain the low rate of recurrent CDI found in this study.…”
Section: Discussionmentioning
confidence: 52%
“…CDI cases in this study exhibited characteristics typical of CDI cases in other regions including advanced age, recent antimicrobial use, treatment with metronidazole and/or vancomycin, and a predominance of HA-CDI among cases. It appears that while the reported prevalence of C. difficile in some Asia-Pacific countries is high [16,17,27], milder outcomes are associated with CDI in the region. In our study, toxic megacolon and colectomy were extremely rare (0.2% and 0.4%, respectively), while all-cause death occurred within 60 days in only 5.2% of cases, compared to 9.3% within 30 days in HA-CDI cases in the USA [28] and 22% within 90 days in a similar European study [29].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, in Kota Bharu, toxin A/B was detected among 9% of 76 hospital inpatients with diarrhea, while toxigenic and nontoxigenic C. difficile were isolated from 13 and 16% of those patients' stool samples. The same study described a low prevalence (2%) of C. difficile colonization in elderly community participants and identified RTs 043 and 017 as the most prevalent strains (14% each among 22 isolates) (8).…”
mentioning
confidence: 95%
“…due to epidemics caused by strains of C. difficile with enhanced virulence such as the CDT-producing strain ribotype (RT) 027, the epidemiology of CDI in the developing countries of Southeast Asia is still understudied. The few reports available describe a lack of awareness among physicians (7,8), a lack of appropriate testing, and a probable underdiagnosis of CDI in the region (9). Frequent unregulated and inappropriate antimicrobial use (10) suggests that the prevalence of CDI could be relatively high.…”
mentioning
confidence: 99%
“…Interestingly, within individual countries, particular types appear to dominate, for example 017 isolates account for 20% of Shanghai isolates whilst in Stockholm, 005 strains are prevalent [49]; in Scotland 078 isolates account for over 10% of infections [50]. Recent studies performed in large tertiary hospitals in Malaysia [51], Indonesia [52] and Thailand [38] underline the importance of using a combined diagnostic approach. In these studies non-toxic strains and those expressing only TcdB were identified when a combination of immunoassays for detection of glutamate dehydrogenase (GDH) and TcdA/B were used.…”
Section: Geographical Distributionmentioning
confidence: 99%